2022
DOI: 10.3390/su142013632
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Waste Palm Cooking Oil Using Immobilized Candida rugosa Lipase

Abstract: Biodiesel production from Waste Palm Cooking Oil (WPCO) is of interest to substitute fossil derived diesel fuel, due to its renewable nature, cleaner emissions and non-toxic properties. Thus, in this study, biodiesel production through transesterification process was optimized using immobilized lipase from Candida rugosa and WPCO collected from the faculty’s cafeteria as a feedstock. Interaction between five operating factors: molar ratio of ethanol to oil, water content, lipase loading, reaction temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…Table 4 shows the biodiesel yields obtained for the transesterification of the waste cooking oil under different reaction conditions. When compared with the results obtained by other authors, the yield values observed here are promising, since 90% was obtained using the fungal enzyme extract, a result which is similar to that achieved in studies that used purified enzymes for the biocatalytic reaction [54,82,88,89].…”
Section: Raw Materials Reaction Conditions (T; A:o; T; A) Biocatalyst...supporting
confidence: 88%
“…Table 4 shows the biodiesel yields obtained for the transesterification of the waste cooking oil under different reaction conditions. When compared with the results obtained by other authors, the yield values observed here are promising, since 90% was obtained using the fungal enzyme extract, a result which is similar to that achieved in studies that used purified enzymes for the biocatalytic reaction [54,82,88,89].…”
Section: Raw Materials Reaction Conditions (T; A:o; T; A) Biocatalyst...supporting
confidence: 88%